National Branding Pariwisata Labuan Bajo Pada Konferensi Tingkat Tinggi (KTT) ASEAN Ke-42 - Fauzi, Reza; Witari, Denik Iswardani (CommLine, 2023)
In Labuan Bajo, there are a number of attractions that could entice visitors from the archipelago and outside. Westmost point of Flores Island is in East Nusa Tenggara (NTT). Labuan Bajo is one of the five Super Priority Tourism Destinations (DPSP) that the government has chosen to as the venue for the 42nd ASEAN Summit. Nation branding generally refers to a country’s strategy to convey a particular image of itself beyond its borders to achieve certain beneficial goals.  The notion is associated with the existence of a "great global market" where countries, cities and regions, compete with each other to attract the largest number of tourists, investors, consumers, students, events and so on. With effective strategies, we can increase the number of tourists visiting an area. The technique of data collection for this study is library research, which is descriptive and qualitative. The results of this study show that encouraging tourism may have a big impact on a region's economic success. With the right advertising, it is possible to boost the number of tourists visiting an area.